“Collaboration with parents isn’t a burden. It’s just a natural part of my work.” - Parental Involvement in Switzerland – An Analysis of Attitudes and Practices of Swiss Primary School Teachers - Egger, Jan; Lehmann, Jürgen; Straumann, Martin (International Journal about Parents in Education, 2023)
The subject of home-school relationship is normatively charged and has increasingly become the focal point of pedagogical discourse in the past years. The article reports results of the project “Home-School Cooperation”, which was supported by the Swiss National Science Foundation. This qualitative study examines, how teachers shape their interaction with parents. The main research question is, which habitualised background convictions guide the interaction of teachers with parents. The data was collected in 10 Swiss primary schools. 39 interviews with teachers and headmasters were transcribed for case reconstructions. They were analysed using sequence analysis according to the method of objective hermeneutics (Oevermann, 2000, 2002a) and interpreted in the tradition of the “Deutungsmusteranalyse” (analyses of patterns of interpretation) (Dewe, 1984). We refer to Oevermann’s theory of professionalisation (Oevermann, 1996, 2002b). Main results are: Teacher–parent cooperation differs as follows: active vs. passive focus on action; dominant client focus; the way the school’s interests is enforced on parents. Teachers show three different interpretations on school–family relationship. “Schools and families as unconnected agents of socialization”; “schools and families as disparate actors of socialization” and “cooperation as a partnership in a professionalised work alliance”. Moreover, seven super-individually interaction patterns can be reconstructed.